Effectiveness of City Branding "Santri City" in Wajo Regency, South Sulawesi Against the Decision of Studying Religion - Elfrianto; Muh. Akbar; Sultan, M. Iqbal (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2024)
This study examines the effectiveness of the Santri City branding in Wajo Regency, South Sulawesi, as part of a strategic effort to shape the region’s image. The research aims to analyze how city branding constructs Wajo Regency’s identity and its impact on public perception, particularly in relation to religious education. Employing a qualitative descriptive analysis, this study explores the conceptualization of Wajo Regency as a brand, considering its multidimensional nature, which includes functional, emotional, relational, and strategic elements. The findings reveal that the Santri City branding effectively enhances the recognition of Wajo Regency as an Islamic educational hub. This strengthened identity influences the decisions of surrounding communities in seeking religious education. Theoretically, this study contributes to the discourse on city branding by highlighting the role of religious identity in shaping regional branding strategies.